INVESTIGATION OF LEARNING STYLE ON SENIOR HIGH SCHOOL LEARNERS - Imas Suparsih (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
It is widely believed that understanding learners’ learning is important it can benefit both learners and teachers because every learner has different learning styles in learning. This study is designed to investigate how learners learn and why they have different learning styles. Qualitative approach was chosen to get in-depth explanation about the issues. Semi structure interview was used as the instrument and it was analyzed descriptively. The finding showed that learning style can be formed by sense experience, environment and learners’ behavior. Further research on investigating of different learning style with more representative sample is recommended. Keywords: investigation, learning style